Post-treatment of Distillery Wastewater after UASB using Aerobic Techniques - Musee, N.; Trerise, M.A.; Lorenzen, L. (South African Journal of Enology and Viticulture, 2016)
The treatment of high-strength wastewater from a distillery using grape-based feedstock was conducted through sequencing the upflow anaerobic sludge blanket (UASB) reactor and the aerobically-activated sludge reactors. The performance of the UASB system was evaluated at the end of a period of 33 days in terms of the final chemical oxygen demand (COD) removal. Final COD removal efficiency of up to 88.7% was achieved. The effect of varying the volumetric loading rates on COD removal was evaluated for the two experimental runs. For run I (undiluted), the volumetric loading rates ranged from 4.06 to 18.90 kg COD/m3.day and the maximum COD removal achieved by the reactor was 57.1%. For experimental run II (diluted), the loading rates ranged between 3.60 to 8.20 kg COD/m3.day, with the reactor achieving 88.7% COD removal. Post-treatment of the effluent using the aerobicallyactivated sludge reactor further improved the overall COD removal in run II to 96.5% and also reduced the phosphorous in the effluent to a final value of approximately 20 mg/L. These experimental results indicate that sequential treatment of the distillery wastewater using UASB followed by aerobically-activated sludge treatment is an efficient system that makes the final effluent compliant with the requirements of environmental legislation.